INTERNALISASI NILAI-NILAI IMAN DAN TAQWA DALAM PEMBENTUKAN KEPRIBADIAN MELALUI KEGIATAN INTRAKURIKULER - Ahmad Khomaini Syafeie (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2020)
AbstractInternalization of the values of iman and taqwa is a process experienced by someone in accepting and making parts of ownership to plant sense textually from religion , as revelation of Allah to achieve his personality steadily. The values of iman and taqwa having become main highlights nowdays. The basic gap, in society of comman secondary education between instructional material and the process of implementing the values of iman and taqwa feels the effect dramatically. This ressearch conducted in Al Azhar Senior high School 5 in Cirebon City by using teachers  as research subject.To avoid misunderstanding of the reserach problem, the writer just identifies research problems on the variables such as tehnique used by teachers in internalizing the values of iman and taqwa and obstacles faced by teachers in internalizing the values of iman and taqwa to their students. In this research he wants to find out the learning signs in internalizing the values of iman and taqwa through intracurricular activities.This research done by using analytic-descriptive method with quantitative approach. Meanwhile the steps to collect the data nedded in this research by using the technique of interview, participative observation, documentation study and questionaire.From the result of this research can be inferred that the techniques conducted by teachers in internalizing the values of iman and taqwa are through intracurricular activity,  such as (1) praying before and after learning process is 75% in good category; (2) reciting Alquran 15 minutes in the first period before learning is 81,7% in excellent category and (3) bringing learning subjects into iman and taqwa loading is 90% in excellent category.The average of learners’ respond based on procentation and category above is 82,2 % in excellent category in internalizing iman and taqwa values conducted by teachers. On the other hand, they must be careful of their effort because of being 17,8% of their students in unstable mood. They need best treatment in improving their lack of things done by teachers.This case indicates any obstacles faced by teacher in internalizing the values and taqwa for students’ personality through intracurricular activities. The obstacles obtained of the activities based on survey, partcipative observation dan documentation are: (1) the measure of class is not adequate; (2) The lack of comprehension of religion subject teachers in bringing learning subjects into iman and taqwa loading; (3) society in which students play is not conducive; and (4) destructive-negative mass media. Keywords:  internalization, iman and taqwa value, personality, intracurricular